Pilot-scale flue gas pyrolysis system for organic and plastic wastes with improved liquid properties in a non-thermal plasma reactor - Lim M.T.; Tan E.S.; Chai Y.H.; Chin B.L.F.; Juwono F.H.; Hisham D.H.B.; Mohamed Anuar M.A. (Elsevier B.V., 2024)
A fast, oxidative pyrolysis system was developed to produce a pyrolysis liquid (PyOL) upgraded with a non-thermal plasma (NTP) reactor. In addition to the 1.8 million tonnes per annum of plastic wastes, large amounts of municipal solid waste in Malaysia end up in landfills, of which 4060 % is organic or food waste. Organic and plastic wastes (OPW) can be used as carbon feedstocks for the pyrolysis process to produce PyOL, reducing the OPW disposal in landfills, and carbon emissions. However, the current pyrolysis methods use pure nitrogen, implying increased operational cost, and are commonly performed at the lab scale. In this study, flue gas was used for the pyrolysis of OPW at a pilot scale. The use of flue gas for PyOL production reduces the operational costs and lifecycle carbon emissions. Results show that the addition of a small percentage of plastics at the pyrolysis temperature of 350 C increased the yield of liquid. However, large amounts of plastics resulted in significant material agglomeration. A disadvantage of PyOL is the degradation of properties with respect to storage time. Therefore, a NTP reactor was developed to improve the PyOL properties. After NTP treatment, the aromatic and carbonyl ester groups decrease, the calorific value increased, and certain chemical compounds increased in concentration. This study provides operational parameters for the pilot scale pyrolysis (and waste-to-energy) process, improving the technical viability of scaling-up such systems. 2023 Elsevier B.V.